2016
DOI: 10.5812/jjm.31598
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis B and C Among Prisoners in Kahramanmaras, Turkey

Abstract: BackgroundHepatitis B virus (HBV) and hepatitis C virus (HCV) infections are among the most important health issues in Turkey. Human immunodeficiency virus (HIV) infections are less frequently observed in the country. The individuals who had blood transfusions, patients undergoing hemodialysis, and intravenous drug addicted individuals, people who had tattoos/piercings, communal living environments, contamination of a family member, and prisoners are the main risk groups.ObjectivesThe current study aimed to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
(26 reference statements)
2
11
1
1
Order By: Relevance
“…Similar results were reported among the prisoners in Turkey by Keten et al, 2016 (14) who found that Anti-HCV was positive in 17.7% but it was higher regarding our HBc antigen seroprevalence as it showed 2.6% HBsAg positivity. Adjei et al, 2006 (15) revealed similar seroprevalence of HCV (19.0%) while the HBsAg recorded 17.4% in prisons in Ghana, the difference in the prevalence of HBV may be attributed to the difference in the marker used for diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported among the prisoners in Turkey by Keten et al, 2016 (14) who found that Anti-HCV was positive in 17.7% but it was higher regarding our HBc antigen seroprevalence as it showed 2.6% HBsAg positivity. Adjei et al, 2006 (15) revealed similar seroprevalence of HCV (19.0%) while the HBsAg recorded 17.4% in prisons in Ghana, the difference in the prevalence of HBV may be attributed to the difference in the marker used for diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Prisoners Prisoners are a vulnerable population and are among the potential priority at-risk populations for micro-elimination [35]. The continued use of drugs and shared syringes, getting new tattoos, and other incidents that cause contact with blood increase the risk of bloodborne infections among prisoners [27]. A national plan formulated jointly by both the Ministry of Health and Ministry of Justice should include training of health-care providers in prisons, screening of prisoners and defining the methodology to access treatment.…”
Section: People With High-risk Behavioursmentioning
confidence: 99%
“…However from the article it is unclear whether the sample was selected from all incarcerated individuals or those presumed to be at higher risk a priori based on nature of the crime leading to incarceration [12]. …”
Section: Prevalence In the Rest Of The Worldmentioning
confidence: 99%